Don't Blame Us : Suburban Liberals and the Transformation of the Democratic Party - Geismer, Lily (Book collections on Project MUSE., 2015)
"Don't Blame Us traces the reorientation of modern liberalism and the Democratic Party away from their roots in labor union halls of northern cities to white-collar professionals in postindustrial high-tech suburbs, and casts new light on the importance of suburban liberalism in modern American political culture. Focusing on the suburbs along the high-tech corridor of Route 128 around Boston, Lily Geismer challenges conventional scholarly assessments of Massachusetts exceptionalism, the decline of liberalism, and suburban politics in the wake of the rise of the New Right and the Reagan Revolution in the 1970s and 1980s. Although only a small portion of the population, knowledge professionals in Massachusetts and elsewhere have come to wield tremendous political leverage and power. By probing the possibilities and limitations of these suburban liberals, this rich and nuanced account shows that--far from being an exception to national trends--the suburbs of Massachusetts offer a model for understanding national political realignment and suburban politics in the second half of the twentieth century"--